Di Balik Layar Penyelundupan: Tokoh-Tokoh dalam Perdagangan Gelap Pemerintah Republik di Singapura, 1947-1949 - Lesta Alfatiana; Ayu Wulandari (Universitas Gadjah Mada, 2022)
This article discusses the figures who were involved in the smuggling of illegal trades carried out by the Republican Government during the revolutionary period of 1945-1949 in Singapore. Illegal trade is one of the Republican Government’s efforts to fill the void of state treasury after the imposition of an economic blockade by the Dutch Government during the revolutionary period. The economic blockade, especially on Sumatra, closed the flow of international trades entering Indonesia. Through this illegal trade, the Republican Government succeeded in filling the void in the state treasury and in providing financial support during the 1945-1949 revolution. However, the process of this illegal trade was carried out with great obstacles and challenges by several figures who made major contributions. Several figures known to have played an important role in this action include Ali Djajengprawira, Utoyo Ramelan, Zairin Zain, Suryono Darusman, R.E. Bajened, Dr. Samad, Joe Loh, Tan Chi Ku, and the last one is Djumbang Roesad.